DKA in patients with pre-existing type 2 diabetes mellitus related to COVID-19: a case series. (5th March 2021) - Ramos-Yataco, Anthony; Meza, Kelly; Cecilia Farfán-García, Reyna; Ortega-Rojas, Solange; Salinas-Mamani, Isaac; Silva-Arrieta Ontaneda, Ivonne; Correa, Ricardo
Summary: The first case of the novel coronavirus infection (COVID-19) in Peru was reported on March 6, 2020. As of September 7, 2020, about 700 000 cases of COVID-19 resulting in 29, 976 deaths have been confirmed by the Ministry of Health. Among COVID-19 patients with co-morbidities, type 2 diabetes mellitus (T2DM) has been recognized as a risk factor for severe disease. Patients with T2DM may experience diabetic ketoacidosis (DKA) and hyperosmolar hyperglycemic (HHS) if infected with the coronavirus 2 (SARS-CoV-2). Regular blood analysis including arterial blood gas is essential in monitoring the care of patients with T2DM infected with COVID-19. We report five cases of DKA in patients with underlying T2DM that presented with severe COVID-19 infection. Learning points: COVID-19 may cause acute metabolic dysregulations in patients with T2DM. It is important to monitor basic metabolic panel (BMP) and arterial blood gases (ABGs) in patients with COVID-19 since metabolic complications can develop unexpectedly. Patients with T2DM develop an inflammatory syndrome characterized by severe insulin resistance and B cell dysfunction that can lead to DKA.